Neutrosophic Analysis of International Diplomacy and Conflict Resolution - Luis Andrés Crespo Berti; Manaces Easud Gaspar Santos; Salomon Alfredo Montecé Giler; Wilder Fabio Ramos Palacios (Neutrosophic Sets and Systems, 2023)
International diplomacy has been essential in resolving conflicts in Ecuador. Throughout its history, it has contributed to resolving border disputes and political tensions at the national and international levels. However, there are factors that can negatively influence these efforts. Despite the challenges, diplomacy will always be vital to maintaining the peace and security of the country. This study focuses on analyzing the role of international diplomacy in conflict resolution in Ecuador and evaluating its impact on the stability of the country and the region. The neutrosophic AHP method was used to obtain the factors that can act as obstacles to carrying out effective diplomacy. It was recognized that internal policy can have a negative impact, so solutions are proposed that can contribute to a more effective approach.